Seed oil and fatty acids of different safflower genotypes and their correlations with agronomic traits and photosynthetic parameters - Guan, L. L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
The differences and interactions between the contents of oil and fatty acids of safflower genotypesintroduced into Ya’an, Sichuan province of China were evaluated, and their relationships with theagronomic traits and photosynthetic parameters were analyzed. Based on the results, the content ofoil percentage ranged from 9.10–24.87%, of palmitic acid from 4.08–7.58%, of stearic acid from 1.42–2.53%, of oleic acid from 8.04–32.96% and of linoleic acid from 59.90–86.70%. Differences in oil contentand fatty acids among genotypes were significant. Oleic acid was significantly correlated with linoleicacid. All correlation coefficients between oil content and fatty acids were nonsignificant. Most of thecorrelation coefficients between agronomic traits and fatty acids were insignificant. Some photosyn-thetic parameters, such as photosynthetic and transpiration rate, were significantly correlated with oilcontent and some fatty acids. This indicated that safflower breeding with high photosynthetic effi-ciency would be an effective way for improving the yield and quality of safflower seed oil.